Protein-Defined Subspecies of HDLs (High-Density Lipoproteins) and Differential Risk of Coronary Heart Disease in 4 Prospective Studies. Issue 11 (November 2020) - Sacks, Frank M.; Liang, Liang; Furtado, Jeremy D.; Cai, Tianxi; Davidson, W. Sean; He, Zeling; McClelland, Robyn L.; Rimm, Eric B.; Jensen, Majken K.
Abstract : Objective: HDL (high-density lipoprotein) contains functional proteins that define single subspecies, each comprising 1% to 12% of the total HDL. We studied the differential association with coronary heart disease (CHD) of 15 such subspecies. Approach and Results: We measured plasma apoA1 (apolipoprotein A1) concentrations of 15 protein-defined HDL subspecies in 4 US-based prospective studies. Among participants without CVD at baseline, 932 developed CHD during 10 to 25 years. They were matched 1:1 to controls who did not experience CHD. In each cohort, hazard ratios for each subspecies were computed by conditional logistic regression and combined by meta-analysis. Higher levels of HDL subspecies containing alpha-2 macroglobulin, CoC3 (complement C3), HP (haptoglobin), or PLMG (plasminogen) were associated with higher relative risk compared with the HDL counterpart lacking the defining protein (hazard ratio range, 0.96–1.11 per 1 SD increase versus 0.73–0.81, respectively; P for heterogeneity <0.05). In contrast, HDL containing apoC1 or apoE were associated with lower relative risk compared with the counterpart (hazard ratio, 0.74; P =0.002 and 0.77, P =0.001, respectively). Conclusions: Several subspecies of HDL defined by single proteins that are involved in thrombosis, inflammation, immunity, and lipid metabolism are found in small fractions of total HDL and are associated with higher relative risk of CHD compared with HDL that lacks the defining protein. In contrast, HDL containing apoC1 or apoE are robustly associated with lower risk. The balance between beneficial and harmful subspecies in a person's HDL sample may determine the risk of CHD pertaining to HDL and paths to treatment. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.